2018
DOI: 10.15640/ijgws.v6n1a8
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor in the Construction of Gender in Media Discourse: Analysis of Metaphors Used to Describe Women in Nigerian newspapers

Abstract: Scholars in linguistic anthropology and discourse analysis (e.g. Zubair, 2007; Mele, 2008) note how gender can be constructed through metaphor. These researchers further argue that metaphor is not just a mere rhetorical ornament or a literary device but rather, a powerful means by which people constitute their social identities and relations. In this paper I report an analysis of the complex and often subtle ways in which some female authors used metaphors to describe women in Nigerian newspapers. I also discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…In the specific case of Spanish, López (2009) concludes that figurative usages of labels such as "vaca" (cow) or "zorra" (vixen) to describe women contribute to normalized social degradation, while Turpin-Moreno (2014) emphasizes that animal imagery conveys negative ideological values in reference to representations of women and their behaviour. In addition to animal imagery, studies on other languages have shown that common frames for women in the news media include objectivizing metaphors such as WOMEN AS BODY PARTS (Chin 2009) or WOMEN ARE COMMODITIES, WOMEN ARE PLANTS, WOMEN ARE A FARMLAND (Ahmed 2018). Some studies focused on the representation of women in academia, showing that the most common metaphors involve the framing of women as strangers/outsiders or mothers/housekeepers (Amery et al 2015).…”
Section: Metaphors Of Womenmentioning
confidence: 99%
“…In the specific case of Spanish, López (2009) concludes that figurative usages of labels such as "vaca" (cow) or "zorra" (vixen) to describe women contribute to normalized social degradation, while Turpin-Moreno (2014) emphasizes that animal imagery conveys negative ideological values in reference to representations of women and their behaviour. In addition to animal imagery, studies on other languages have shown that common frames for women in the news media include objectivizing metaphors such as WOMEN AS BODY PARTS (Chin 2009) or WOMEN ARE COMMODITIES, WOMEN ARE PLANTS, WOMEN ARE A FARMLAND (Ahmed 2018). Some studies focused on the representation of women in academia, showing that the most common metaphors involve the framing of women as strangers/outsiders or mothers/housekeepers (Amery et al 2015).…”
Section: Metaphors Of Womenmentioning
confidence: 99%
“…Logos: Revista de Lingüística, Filosofía y Literatura 31 (2) Entre los distintos elementos que pueden ser comprendidos y construidos a través de la metáfora, se encuentra la propia identidad de las personas (Ahmed, 2018). En esta visión, la metáfora no es prescindible en el discurso.…”
Section: La Metáfora En Los Estudios De Discursounclassified
“…The concept of "sex" refers only to the anatomical and biological structure of men and women, and the concept of "gender" is a set of sociocultural values designed by society and identified with representatives of the male and female sexes (Arustamyan, Makurina, & Pirozhkova, 2016). Gender values have national specificity and are of great importance in the process of creating ideas about the ideal embodiment of "masculinity" and "femininity" in any culture (Ahmed, 2018). These representations play a large role in the formation of public consciousness and have an impact on a person's ability to perceive the world, on human behavior and speech acts.…”
Section: 2mentioning
confidence: 99%